ERRATUM of Issue 33 JCMC 2020 - Chitwan Medical College, Journal of (Journal of Chitwan Medical College, 2020)
The online and print version of the “Knowledge, attitude and practice of self-medication among medical students during exam time”(Bhattarai AK, Karki PK. Knowledge, attitude and practice of self-medication among medical students during exam time. Journal of Chitwan Medical College.2020;10(33):25-8.) has been updated according to the respective authors’ reply published in JCMC 33 Issue. Following correction has been done: Department of the co author Prabin Kumar Karki should be Physiology instead of Biochemistry.